Politik Pendidikan dalam Adaptabilitas Mahasiswa Ilmu pemerintahan FISIP UPR dalam Memenuhi Kuliah Daring di Masa Pandemi Covid 19 - Purnama Julia Utami; Yunita Asmawati (Prodi Sosiologi FISIP UPR, 2020)
19 arrived, education was carried out using the traditional method of face-to-face, however, The Covid has hit education since March 2020 by changing the basic offline method of learning to virtually. This article will elaborate on how covid 19 brings some adaptable process changes for lecturers and students in fulfilling and completing virtual lectures for a year. The author will focus on the struggle of lecturers and students in completing bureaucracy as their responsibilities as well as the abilities and the limitations of students in fulfilling lectures. In contrast to the offline method of learning, the main argument from this paper is how that lectures will be more expensive along with the only using virtually. Still, the bureaucracy must be continuing the education processes, even though with the minimally facilities. As a result, there will be negotiations between bureaucracy, educators, and students in strengthening their existence.